2019
DOI: 10.17219/acem/106173
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of non-alcoholic fatty liver disease: Polish-case control study

Abstract: Background. Non-alcoholic fatty liver disease (NAFLD) is becoming the most common cause of chronic liver disease worldwide, affecting up to 30% of population. Non-alcoholic fatty liver disease can lead to non-alcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and hepatocellular carcinoma. Age, obesity, insulin resistance, type 2 diabetes, and dyslipidemia are important risk factors for developing hepatic steatosis. Concomitant diseases, especially cardiovascular, are discussed as important causes of death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Data on the association of diverticulosis and fatty liver disease are conflicting. While Bae et al and Kempinski et al showed a correlation between increasing levels of fatty liver and diverticulosis (moderate FLD (OR 2.238; 95% CI 1.026–4.882); severe FLD (OR 5.519; 95% CI 1.236–21.803)) [ 39 , 42 ], Sahin et al identified fatty liver disease as a negative predictor of diverticulosis (OR 0.529; 95% CI 0.323–0.866) [ 43 ]. Interestingly patients in the latter study were 65 years or older, while Bae et al and Kempinski et al included younger patients.…”
Section: Resultsmentioning
confidence: 99%
“…Data on the association of diverticulosis and fatty liver disease are conflicting. While Bae et al and Kempinski et al showed a correlation between increasing levels of fatty liver and diverticulosis (moderate FLD (OR 2.238; 95% CI 1.026–4.882); severe FLD (OR 5.519; 95% CI 1.236–21.803)) [ 39 , 42 ], Sahin et al identified fatty liver disease as a negative predictor of diverticulosis (OR 0.529; 95% CI 0.323–0.866) [ 43 ]. Interestingly patients in the latter study were 65 years or older, while Bae et al and Kempinski et al included younger patients.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis showed that individuals with GERD had approximately twice the risk of developing NAFLD compared to those without GERD ( 12 ). A case–control study conducted in Poland also found a higher susceptibility of NAFLD among patients with GERD ( 34 ). GERD may promote the development of NAFLD through multiple mechanisms.…”
Section: Discussionmentioning
confidence: 97%
“…Although there is a lack of evidence regarding the interrelation between colonic diverticulosis and NAFLD, it has been suggested that these two disorders commonly co-exist and share several traits of MetS [19]. Kempi ński et al reported concomitant colonic diverticulosis as the second most frequent gastrointestinal disease along with NAFLD (after gastroesophageal reflux disease) that was more prevalent in the patients' group than in the controls (23.7% vs. 15.8%; p < 0.005) [20], while Bae et al reported a higher overall prevalence of fatty liver in colonic diverticulosis patients (69.7%) as compared to the results of this study [21]. Additionally, the evaluated characteristics of metabolic dysregulation (fasting glucose, systolic blood pressure, triglycerides, total cholesterol, and CRP) were more prominent in colonic diverticulosis patients in whom hepatic steatosis was detected.…”
Section: Discussionmentioning
confidence: 99%